3D simulations of flow past a cylindrical bridge pier for determination of drag coefficient as a function of Froude number - Novak, Gorazd (Acta hydrotechnica, 2025)
Increasingly frequent floods demonstrate the vulnerability of bridges and their piers. Designing a pier involves determining its drag coefficient C_d. In the existing literature, C_d is given as a function of the Reynolds number Re, i.e. C_d=f(Re), while the present study also investigated C_d as a function of the Froude number Fr, i.e. C_d=f(Fr). The SPH method and the model DualSPHysics were used to simulate three-dimensional turbulent free-surface flows past a surface-piercing cylinder in a straight horizontal channel. Subcritical, critical, and supercritical flows with Fr<2 were examined. The model was calibrated for flows in a duct filled with water (i.e. flows without free water surface) and validated against open channel experiments from the literature. Finally, the model was used to simulate real-life high-discharge conditions. Determination of C_d=f(Fr) indicated that the constant value of C_d as defined in the Eurocode 1 standard is not necessarily optimal.
Keywords: 3-D model; 3D-model; bridge pier; drag coefficient; DualSPHysics; koeficient upora; mostni opornik; SPH; SPH, DualSPHysics